High time for heroes - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2014)
"Jack and Annie are magically transported to mid-1800's Thebes where they are saved from a dangerous accident by Florence Nightingale!"--
Keywords: Nightingale, Florence, -- 1820-1910 -- Fiction; Time travel -- Fiction; Magicians -- Fiction; Nurses -- Fiction; Tree houses -- Fiction; Thebes (Egypt : Extinct city) -- Fiction